Post-Diagnostic Aspirin Use in Breast Cancer Treatment: A Systematic Review and Meta-Analysis of Survival Outcomes with Trial Sequential Analysis Validation - Po-Huang Chen; Tung-Lung Yang; Hong-Jie Jhou; Hsu-Lin Lee; Ming-Shen Dai (Diagnostics)
Background: Breast cancer is a leading cause of cancer-related mortality in women. Aspirin, an affordable anti-inflammatory drug, may have anticancer effects, but its impact on survival outcomes after breast cancer diagnosis remains unclear. This meta-analysis evaluates the role of post-diagnostic aspirin use in breast cancer management. Methods: A systematic review and meta-analysis were conducted using PubMed, EMBASE, and Cochrane Library databases. Twenty studies involving 141,251 participants were included. Survival outcomes assessed were disease-free survival (DFS), overall survival (OS), and breast cancer-specific mortality. Trial sequential analysis (TSA) was used to evaluate the sufficiency of cumulative evidence. Results: Post-diagnostic aspirin use was not significantly associated with DFS (HR: 0.88; 95% CI: 0.69–1.11) or OS (HR: 0.89; 95% CI: 0.74–1.07). However, a significant reduction in breast cancer-specific mortality was observed (HR: 0.77; 95% CI: 0.63–0.93). TSA confirmed that the evidence supporting this association is sufficient. Conclusions: Post-diagnostic aspirin use significantly reduces breast cancer-specific mortality, but it does not improve DFS or OS. These findings underscore the potential therapeutic role of aspirin in breast cancer management. Further randomized controlled trials are needed to validate these results and determine optimal dosing regimens for post-diagnostic use.